OPTIMASI BIOGAS DENGAN PENAMBAHAN LIMBAH KULIT NANAS BERBANTU GELOMBANG MIKRO - Sufrotun Khasanah; Safaah Nurfaizin (Fakultas Teknik dan Rekayasa, 2024)
Zero net emission has become a global issue that is being discussed intensively along with the development of technology to the point of giving birth to various policies that have been issued by many countries in the world. One way to realize this is by diversifying green energy. Bio energy is the right solution to achieve this global goal, namely the utilization of pineapple skin waste as raw material for biogas production. so it is very appropriate to conduct research to examine the effect of adding pineapple skin waste to increase biogas production with microwave treatment and process optimization. The optimum condition of the temperature variable obtained the best results at a temperature of 900C with a cellulose solubility of 29.42%, while the lignin solubility obtained was 9.05% which can be concluded that MAE pretreatment can increase the solubility of the cellulose and lignin composition. Furthermore, the optimum condition for biogas production was produced in pineapple skin samples with MAE treatment with a ratio of 1:2 (w/v) of 917mL. From the research that has been carried out, it shows that along with the increase in total solids entered into the biodigester, the amount of biogas production produced will increase.